PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI - Andrika, Oktavia; Atmazaki, Atmazaki; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACT The purpose of this study is to describe the influence of cooperative learning model of jigsaw type toward writing description text skill for student at Seventh grade in 12 Junior High School Padang (SMP Negeri 12 Padang). This research is a quantitative study with experimental method. The study design is a static two groups. The population in this study is a class VII SMP Negeri 12 Padang totaling 262 people. Samples were determined using purposive sampling technique which consists of two classes, without using the model of cooperative learning type jigsaw (VII.4 class) totaling 34 students, and classes using model of cooperative learning type jigsaw (class VII.5) totaled 32 students. Instruments used in this research that tests the performance. The data of this study is score of the test result writing description text skill by using cooperative learning model of jigsaw type. The data was collected through work showing test. Based on data analysis, the use of cooperative learning model of type jigsaw affect the description text writing skills for students at seventh grade in 12 junior high school Padang at the significance level of 95% with dk = (n1 + n2) -2.Kata kunci: pengaruh, pembelajaran kooperatif, jigsaw, teks menulis deskriptif